Diseases of man acquired from his pets - Bisseru, Balideo (Heinemann Medical, 1967)
Diseases of Man Acquired from his Pets provides guideline of the diseases that man may acquire from animals. This book is composed of nine chapters. The chapters are divided broadly into the types of animals kept as pets. This book begins with a general introduction to animal pets. The subsequent chapters deal with diseases acquired from carnivores, birds, and rodents, with a particular emphasis on leptospirosis, which affects rodents, carnivores, farm animals, man and, to a limited extent, birds. These chapters discuss the epidemiology, clinical signs, symptoms and treatment of this infection.